Conventional and unconventional secretory proteins expressed with silkworm bombyxin signal peptide display functional fidelity. Issue 1 (December 2017) - Park, Sungjo; Arrell, D.; Reyes, Santiago; Park, Enoch; Terzic, Andre
Abstract Growth factors are signaling molecules which orchestrate cell growth, proliferation and differentiation. The majority are secreted proteins, exported through the classical endoplasmic reticulum (ER)/Golgi-dependent pathway, but a few are released by unconventional ER/Golgi-independent means. Human fibroblast growth factor 2 (FGF2) and insulin-like growth factor 1 (IGF1), are canonical prototypes secreted by the unconventional and conventional pathway, respectively. We herein examined whether expression of these two growth factors in theBombyx mori nucleopolyhedrovirus (BmNPV)-based silkworm expression system with its innate signal peptide, bombyxin, secures structural homogeneity at the signal peptide cleavage site regardless of the native secretory route. Proteomic analysis mapped structural microheterogeneity of signal peptide cleavage at the amino terminus of FGF2, whereas IGF1 displayed homogeneous amino-terminal cleavage with complete removal of the bombyxin signal peptide. A cell proliferation assay revealed potent functional activity of both FGF2 and IGF1, suggesting that FGF2 amino-terminal microheterogeneity does not alter mitogenic activity. These findings demonstrate that the occurrence of amino-terminal structural homogeneity may be associated with the original secretion mechanism of a particular growth factor. Furthermore, our results highlight the bombyxin signal peptide as a reliable secretion sequence applicable to mass production of functionally active secretory proteins in a silkworm-based expression platform.